EU-type carbon emissions trade and the distributional impact of overlapping emissions taxes - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
The European Union fulfills its emissions reductions commitments by means of an emissions trading scheme covering some part of each member state's economy and by national emissions control in the rest of their economies. The member states also levy energy/emissions taxes overlapping with the trading scheme. Restricting our focus on cost-effective policies, this paper investigates the distributive consequences of increasing the overlapping emissions tax that is uniform across countries. For quasi-linear utility functions and for a class of parametric utility and production functions emissions tax increases turn out to be exactly offset by permit price reductions. As a consequence permit-exporting [permit-importing] countries lose [gain] from an increase in the emissions tax. These results are not general, however. By means of a numerical example we show that export-import reversals and welfare reversals are possible.
Keywords: H21; H22; Q56; 330; emissions taxes; emissions trading; international trade; Ökosteuer; Steuerinzidenz; Emissionshandel; Außenhandel; Wohlfahrtseffekt; Theorie; EU-Staaten